Coronavirus disease 2019 and the young heart: prevention, treatment, and return to play. Issue 5 (29th October 2022) - Beach, Cheyenne M.; Faherty, Erin; Pesce, Meredith
Abstract : Purpose of review: COVID-19-related guidance has changed dramatically since the onset of the pandemic. Awareness of data regarding prevention of disease, the cardiac manifestations and treatment of acute COVID-19 and multisystem inflammatory syndrome in children, and return to physical activity following an infection allows for appropriate adjustment of current care models and guides future study. Recent findings: Severe acute respiratory syndrome coronavirus 2 transmission can be reduced using various mitigation strategies, though their effectiveness differs based on viral prevalence. The risk of severe disease during acute COVID-19 infection is low in children and adolescents, though specific risk factors have been identified. COVID-19 vaccination significantly decreases the risk of severe disease and poor outcomes. Regular physical activity positively affects well being and has been a focus of recent guidance regarding well tolerated return to activities following an infection. Summary: The use of strategies to reduce viral transmission will depend on individuals' and communities' risk tolerance and on current viral prevalence. COVID-19 vaccination should be encouraged, particularly in patients with identified risk factors. Allowing children and adolescents to safely participate in physical and other activities should continue to be a focus of our clinical and research efforts given their myriad benefits in this population.